Reliable and Energy Efficient Streaming Multiprocessor Systems - Das, Anup Kumar; Kumar, Akash; Veeravalli, Bharadwaj; Catthoor, Francky; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book discusses analysis, design and optimization techniques for streaming multiprocessor systems, while satisfying a given area, performance, and energy budget. The authors describe design flows for both application-specific and general purpose streaming systems.  Coverage also includes the use of machine learning for thermal optimization at run-time, when an application is being executed.  The design flow described in this book extends to thermal and energy optimization with multiple applications running sequentially and concurrently.
Chapter 1. Introduction -- chapter 2.Operational Semantics of Application and Reliability Model -- Chapter 3.Literature Survey on System-level Optimizations Techniques -- Chapter 4.Reliability and Energy-Aware Platform-Based Multiprocessor Design -- Chapter 5.Reliability and Energy-Aware Co-design of Multiprocessor Systems -- Chapter 6.Design-time Analysis for Fault-Tolerance -- Chapter 7.Run-time Adaptations for Lifetime Improvement -- chapter 8.Conclusions and Future Directions.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Logic design; Electronic Circuits and Systems; Processor Architectures; Logic Design